Ambulatory EEG-video - González Otárula, Karina A.; Schuele, Stephan (Epilepsy & behavior, 2024)
•Ambulatory EEG (AEEG) is a technique that consists of a portable prolonged EEG recording that can be performed with or without video.•Recent guidelines were published on the minimum technical requirements for AEEG.•AEEG has a place in epilepsy diagnosis and classification, events recording and classification and epilepsy management.•Ultra-long ambulatory monitoring is a promising technology. Hospital based EEG recordings have been the norm to assist in the diagnosis and management of patients with unclassified events and known drug resistant epilepsy. Ambulatory EEG (AEEG) is a tool that comes to serve the needs for a portable testing that can be done at home, often with higher accessibility compared to an epilepsy monitoring unit and with lower cost. The current technology provides good quality EEG tracing and can be done with video when needed. In this review we discuss how AEEG should be performed and the preferred indications in which this test may be of utmost help. The advent of ultra-long ambulatory recording may be the future for selected patients as this technology evolves.